An Effective Approach for Musical Theatre Curriculum in Pedagogical Innovation - Jialin Li; Hyuntai Kim (Malikussaleh University, Aceh, Indonesia, 2025)
Musical theatre education necessitates a flexible and well-structured curriculum that combines creative instruction, theoretical knowledge, and current pedagogical practices. However, many existing curricula continue to face challenges, such as limited resource allocation, a lack of adaptive learning strategies, and insufficient opportunities for personalized learning paths. These gaps often lead to poor student performance, low engagement, and unsatisfactory feedback from instructors. To address these issues, this study introduces the Musical Theatre Curriculum Planning Algorithm (MTCPA). This curriculum optimization framework combines adaptive learning with a project-based approach, leveraging traditional, digital, and experiential learning sources. The MTCPA was evaluated using a dataset of 200 students that incorporated blended learning methods, gamification elements, and AI-assisted feedback mechanisms. The instructional materials were divided into three main categories: acting, singing, and dancing. The framework's effectiveness was measured using key indicators, including student performance outcomes, engagement levels, and instructor evaluations. The results show significant improvements: student performance scores increased by 27%, engagement levels increased by 35%, resource utilization increased by 40%, and teacher satisfaction with the curriculum design increased by 30%. The proposed algorithm not only improves classroom performance but also enhances long-term skill retention through practical application, promoting early career readiness in the competitive fields of musical theatre and the performing arts. Furthermore, the data-driven, adaptive nature of MTCPA enables a structured yet innovative approach to curriculum planning, leading to more effective decision-making and pedagogical creativity. To summarize, the MTCPA represents a significant step forward in musical theatre education, demonstrating how incorporating adaptive, personalized, and technology-supported learning can result in measurable improvements in student success, engagement, and curriculum efficiency. By combining traditional methods with modern innovations, MTCPA helps to reshape musical theatre pedagogy, ensuring that students are better prepared to face both academic and professional challenges in the performing arts.